(untitled) (Fiep Bulletin - online, 2015)
Plural gender is the reference of the following study, under the perspective of the sexual difference. Aware of the masculine/feminine determination in the society we analyse the masculine/feminine construction in the Physical Education classes. Methodologically we based ourselves on Stake (1998), concerning the study of the qualitative case. We observed a high school class at Júlio Mesquita State School, in the city of Curitiba, Paraná. We focused on the teachers’ interventions, on the contents, on the spaces filled by both sexes, on the relationship between boys and girls, among themselves and in mixed groups. The results showed that the teachers acted inside restrictive models in the masculine symbolic world, contributing to the unilateral education of the patriarchal perspective. In short, we have understood that the mixed classes, in the studied case, didn’t provide activities and spaces that motivated the feminine in the classes. The pedagogical references didn’t permit the feminine recreation in the school atmosphere as well as restricted the masculine expressions in the Physical Education classes.